The Contribution of Capital to Economic Growth - Denison, Edward (American Economic Review, 2016)
How important to economic growth in advanced countries is the accumulation of physical capital? My short answer is that increased capital is one of several important sources of output growth. This appraisal, which is amply supported by research results, should surprise no one-but doubtless it will. Capital is not the source of growth despite the contrary view common in financial circles and on Capitol Hill. Output, and therefore growth, are governed by many determinants. Moreover, there is no substance to the recurring notion that the United States' growth rate would have matched those of countries like Germany or Japan if only we invested as much as they did. Finally, it is quite wrong to blame investment for the recent sharp reduction in the growth of American output and productivity, or to suppose that merely raising investment would go far toward restoring the old growth rate of productivity. Why many people share a vision of growth that assigns exclusive attention to capital I do not know. Growth models that feature capital, while assigning other output determinants to ceteris paribus, may be partly responsible, but it should have been apparent to all that such models were meant only to illuminate a relationship, not to describe a whole economic system. Analyses based on incremental capital-output ratios may have contributed to the illusion. If so, as Robert Solow says of these ratios, Economists have a responsibility to do better. To deny that capital is everything is not to imply that it is nothing. I do not share the other extreme view, sometimes encountered, that capital can be ignored because its significance is hard to establish if one fits a production function by correlation analysis. I stress again: capital is an important growth source. It has sometimes contributed importantly to differences in growth rates between periods and places. More capital formation would raise the growth rate. The contribution of capital to growth is evaluated best in the context of a complete analysis of the sources of growth. The following summary, drawn from my Accounting for Slower Economic Growth, refers to total potential national income originating in nonresidential business. During the period from 1948 to 1973 the growth rate of this series was 3.8 percent per year. Of that amount, 15 percent resulted from more capital, that is, more nonresidential structures and equipment and more inventories. Another 15 percent is ascribed to changes in employment and working hours, with account also taken of the age-sex composition of workers. Fourteen percent was due to increased capabilities of workers resulting from more education. Ten percent resulted from improved resource allocation, taking the form of a reduction in the amount of labor overallocated to farming and to self-employment and unpaid family labor in nonfarm establishments too small for efficiency. Thirty-seven percent was contributed by advances in technological, managerial, and organizational knowledge as to how to produce at low cost, together with miscellaneous output determinants not separately estimated. This is the residual in the calculation. In the 1948-73 period it probably provides a tolerable approximation to the contribution of advances in knowledge alone. If so, advances in knowledge were much the largest single source of growth. Economies of scale made possible by the growth of markets contributed an estimated 11 percent of the growth rate. Finally, certain changes in the legal and human environment, together with irregular factors, subtracted 2 percent. *Associate Director for National Economic Accounts, Bureau of Economic Analysis.